PENGEMBANGAN LKPD BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEBHINEKAAN GLOBAL PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS VI SD - Fathia Filma Nukiki; Joko Siswanto; Sumarno (Journal of Education Reseach and Evaluation, 2025)
The current issue faced by students is their lack of familiarity with their own culture, as they tend to perceive it as outdated. Based on this concern, the purpose of this study was to develop a student worksheet (LKPD) based on local wisdom. This research employed a Research and Development (R&D) approach, using the ADDIE model as the development framework. The research subjects consisted of material experts, assessment experts, and practitioners, while the trial subjects were sixth-grade elementary school students. Data were collected through tests, questionnaires, and documentation. The research instruments included questionnaire sheets and test items. Data analysis techniques involved qualitative descriptive analysis, quantitative analysis, and inferential statistics. The results showed that the validation score of the LKPD by material experts was 93.06, categorized as highly valid. The validation score by assessment experts was 94.29, also categorized as highly valid. The small-scale trial yielded a score of 86.11, indicating the highly practical category. The evaluation provided by practitioners resulted in a score of 94.32, also categorized as highly practical. Meanwhile, the peer evaluation obtained a score of 90.91, likewise classified as highly practical. Furthermore, the t-test results indicated a significant difference between the pretest and posttest means. The n-gain analysis for sixth-grade students on the global diversity indicator yielded an average n-gain score of 0.408, which falls into the moderate category. In conclusion, the LKPD based on local wisdom developed in this study has been proven to be valid, practical, and effective, making it highly suitable for use in Pancasila Education learning at the elementary school level to enhance students’ attitudes of respect and responsibility.